Selection of superior assamica tea clones with high yield potential and high catechine contents - Sriyadi, Bambang (Research Institute for Tea and Cinchona, 2012)
Selection of superior assamica tea clones with high yielding potential and high catechine contents, was conducted using plant materials of selected mothers bushes from F1 polyclonal seed field with a clone composition of Kiara 8, TRI 777, TRI 2024, TRI 2025, and PS 1. The selected bushes had a minimum 100 g per bush. This research was conducted in Pasir Sarongge Experimental Garden, representing medium elevation and Gambung Experimental Garden, representing high elevation. Experimental design in each location was a randomized complete block design with three replications. Twenty five selected clones were used in this research with one high yielding GMB 7 as a check. Plot contained 15 bushes with plant distant of 120 x 80 cm. Shoot yield were observed in September to November 2010 on six years old plant of third prunning stages with plucking cycle seven days. Catechine content of clone were observed by extracting dry tea shoot in boilling water, followed by deluting in ethyl acetate and HPLC readings. The results showed that in medium elevation clone number of II.32.15 had similar yielding potential with GMB 7 clone with catechine content 16,44%, and at high elevation clones number of II.6.10, III.28.4, III.35.3, and III.36.15 had high yielding potential and catechine content of 15,35%; 16,13%; 16,03%; and 13,14% respectively